Arachidonic Acid in Follicular Fluid of PCOS Induces Oxidative Stress in a Human Ovarian Granulosa Tumor Cell Line (KGN) and Upregulates GDF15 Expression as a Response - Ma, Yalan; Zheng, Lianwen; Wang, Yeling; Gao, Yiyin; Xu, Ying (Frontiers in Endocrinology, 2022)
Polycystic ovarian ovary syndrome (PCOS) is the main cause of ovulatory infertility and a common reproductive endocrine disease of women in reproductive age. In addition, nearly half of PCOS patients are associated with obesity, and their total free fatty acids tend to increase. Arachidonic acid (AA) is a polyunsaturated fatty acid. Oxidation products of AA reacting with various enzymes[cyclooxygenases (COX), lipoxygenases (LOX), cytochrome P450s (CYP)]can change cellular mitochondrial distribution and calcium ion concentration, and increase reactive oxygen species (ROS) production. In this study, we analyzed the follicular fluid fatty acids and found higher levels of C20:4n6 (AA) in PCOS patients than in normal control subjects. Also, to determine whether AA induces oxidative stress (OS) in the human ovarian granulosa tumor cell line KGN and affects its function, we treated KGN cells with or without reduced glutathione (GSH) and then stimulated them with AA. The results showed that AA significantly reduced the total antioxidant capacity (TAC) and activity of antioxidant enzymes and increased the malondialdehyde (MDA), ROS and O2- levels in KGN cells. In addition, AA was also found to impair the secretory and mitochondrial functions of KGN cells and induce their apoptosis. We further investigated the downstream genes affected by AA in KGN cells and its mechanism of action. We found that AA upregulated the expression of growth differentiation factor 15 (GDF15), which had a protective effect on inflammation and tissue damage. Therefore, we investigated whether AA-induced OS in KGN cells upregulates GDF15 expression as an OS response. Through silencing of GDF15 and supplementation with recombinant GDF15 (rGDF15), we found that GDF15, expressed as an OS response, protected KGN cells against AA-induced OS effects, such as impairment of secretory and mitochondrial functions and apoptosis. Therefore, this study suggested that AA might induce OS in KGNs cells and upregulate the expression of GDF15 as a response to OS.